Influences of Medical Crowdfunding Website Design Features on Trust and Intention to Donate: Controlled Laboratory Experiment - Zhang, Xing; Hu, Wenli; Xiao, Quan (JMIR Publications, 2021)
BackgroundAs a type of donation-based crowdfunding, medical crowdfunding has gradually become an important way for patients who have difficulty paying medical bills to seek help from the public. However, many people still have limited confidence in donating money to medical crowdfunding projects. ObjectiveGiven that the features of a medical crowdfunding website may be important to gain users' trust, this study draws upon two-factor and trust theories to explore how different design features of medical crowdfunding websites affect potential donors' cognition-based trust and affect-based trust, and how these types of trust affect the intention to donate. MethodsA 2 (informativeness: high vs low) × 2 (visual cues: cool color vs warm color) × 2 (social cues: with vs without) between-subject laboratory experiment was performed to validate our research model. A total of 320 undergraduate students recruited from a university in China participated in the controlled laboratory experiment. ResultsCognition-based trust (β=.528, P<.001) and affect-based trust (β=.344, P<.001) exerted significant effects on the intention to donate of potential donors of medical crowdfunding. Informativeness as a hygiene factor positively influenced potential donors' cognition-based trust (F1,311=49.764, P<.001) and affect-based trust (F1,311=16.093, P<.001), whereas social cues as a motivating factor significantly influenced potential donors' cognition-based trust (F1,311=38.160, P<.001) and affect-based trust (F1,311=23.265, P<.001). However, the color of the webpages affected the two dimensions of trust differently. Specifically, medical crowdfunding webpages with warm colors were more likely to induce affect-based trust than those with cool colors (F1,311=17.120, P<.001), whereas no significant difference was found between the effects of cool and warm colors on cognition-based trust (F1,311=1.707, P=.19). ConclusionsThis study deepens our understanding of the relationships among the design features of medical crowdfunding websites, trust, and intention to donate, and provides guidelines for managers of medical crowdfunding platforms to enhance potential donors' trust-building by improving the website design features.